Toward the Design of High‐performance Supercapacitors by Prussian Blue, its Analogues and their Derivatives. Issue 3 (17th August 2020) - Lin, Yueqiang; Zhang, Longhai; Xiong, Ya; Wei, Tong; Fan, Zhuangjun
Abstract : Supercapacitors (SCs) with high power output have attracted increasing attention as efficient and environmentally friendly energy storage devices. Prussian blue and its analogues (PB/PBAs) are simple coordination polymers with tunable chemical compositions and open framework. Prussian blue can act as electrode materials in its pristine form and has also been utilized to derive various metallic nanostructures for electrochemical applications due to their simple fabrication process, non‐toxic characteristics, and low price. Here, we firstly describe the charge storage mechanisms of SCs briefly followed by an introduction of the fabrication methods of PB/PBAs and their derivatives. Then, a comprehensive review on recent studies of the use of PB/PBAs and their derivatives as the electrode materials for SCs are given with a focus on strategies to improve their electrochemical performances. Finally, we discuss critical challenges in this research area and propose some general ideas for future research. Abstract : Prussian blue and its analogues (PB/PBAs) are simple coordination polymers with tunable chemical compositions and open framework. Prussian blue can act as electrode materials in its pristine form and has also been utilized to derive various metallic nanostructures for electrochemical applications due to their simple fabrication process, non‐toxic characteristics, and low price. PB/PBAs and their derivatives are promising and widely used electrode materials for supercapacitors.